Targeted transcriptomic analysis of pancreatic adenocarcinoma in EUS-FNA samples by NanoString technology - Pedrosa, L.; Araujo, I. K.; Cuatrecasas, M.; Soy, G.; López, S.; Maurel, J.; Sánchez-Montes, C.; Montironi, C.; Saurí, T.; Sendino, O.; Pérez, F. M.; Ausania, F.; et al. (Frontiers in Molecular Biosciences, 2023)
BACKGROUND: Integration of transcriptomic testing into EUS-FNA samples is a growing need for precision oncology in pancreatic ductal adenocarcinoma (PDAC). The NanoString platform is suitable for transcriptome profiling in low yield RNA samples. METHODS: Inclusion of patients that underwent EUS-FNA cytological diagnosis of PDAC using 19G and/or 22G needles and subsequent surgical resection. Formalin fixed paraffin embedded (FFPE) cytological and surgical samples underwent RNA extraction and transcriptomic analysis using a custom 52-gene NanoString panel of stromal PDAC features. Cell type abundance was quantified in FFPE specimens and correlated. RESULTS: 18 PDAC patients were included. Mean EUS-FNA passes was 2 + 0.7. All FFPE passed the RNA quality control for genomic analysis. Hierarchical clustering on the global gene expression data showed that genes were differentially expressed between EUS and surgical samples. A more enriched CAF and EMT transcriptomic profile was observed across surgical specimens whereas immunological biomarkers were more represented in EUS-FNA samples. Cytological examination confirmed a scanty representation of CAF and more immunological cell abundance in cytological samples in comparison to surgical specimens. CONCLUSIONS: Targeted transcriptomic NanoString profiling of PDAC samples obtained by EUS-FNA is a feasible approach for pre-surgical molecular analysis although stromal CAF/EMT mRNA biomarkers are underrepresented.